Body Temperature, Blood Infection Parameters, and Outcome of Thrombolysis-Treated Ischemic Stroke Patients. Issue 8 (December 2013) - Tiainen, Marjaana; Meretoja, Atte; Strbian, Daniel; Suvanto, Joel; Curtze, Sami; Lindsberg, Perttu J.; Soinne, Lauri; Tatlisumak, Turgut; ,
Background and Aims: Body temperature, inflammation, and infections may modify response to thrombolytic therapy. We studied their associations with clinical improvement after intravenous thrombolysis and three-month outcome. Methods: We included 985 consecutive acute ischemic stroke patients treated with intravenous thrombolysis at the Helsinki University Central Hospital during 1995–2008. Body temperature, blood leukocyte count, and C-reactive protein levels were analyzed on arrival and at day one. Clinical improvement was defined as National Institutes of Health Stroke Scale score decrease of ≥4 points or a score of 0 at 24 h. Functional outcome was assessed at three-months with the modified Rankin Scale dichotomized at 0–2 (good) vs. 3–6 (poor). Associations were tested with multivariable logistic regression analysis. Results: Of the baseline variables, lower C-reactive protein independently predicted clinical improvement at 24 h (odds ratio 0·94 per 5 mg/L; 95% confidence interval 0·89–1·00; P = 0·03), whereas higher leukocyte count (odds ratio 1·10 per E9/L; 1·03–1·17; P < 0·01) and C-reactive protein (odds ratio 1·07 per 5 mg/L; 1·01–1·14; P = 0·02) were associated with poor three-month outcome. When body temperature increased over the first 24 h, clinical improvement after thrombolysis was unlikely (odds ratio 0·66 per °C; 0·45–0·95; P = 0·03) and poor outcome more common (odds ratio 1·63 per °C; 1·24–2·14; P < 0·001). Elevated leukocytes at baseline increased the risk of symptomatic intracerebral hemorrhage (odds ratio 1·07 per E9/L; 1·00–1·13; P = 0·04). Conclusion: A lower level of systemic inflammation at time of thrombolysis may be associated with clinical improvement and good outcome at three-months. Increase in body temperature during the first 24 h associates with lack of clinical improvement and worse patient outcome.